Four new species of the subterranean amphipod genus Stygobromus (Amphipoda: Crangonyctidae) from shallow groundwater habitats on the Coastal Plain and eastern margin of the Piedmont in Maryland and Virginia, USA - Holsinger, John R.; Ansell, Lynnette Meador; Shafer, Justin (Zootaxa, 2011)
Four new species of the subterranean amphipod genus Stygobromus are described from groundwater habitats in Maryland and Virginia. All four of the species occur in Maryland, and one of them also occurs in Virginia.Three of these species are found in groundwater seeps or seepage springs in the Piedmont of northeastern Maryland, whereas the fourth occurs in similar habitats on the Coastal Plain of southern Maryland west of the Chesapeake Bay and on the opposite side of the Potomac River in seeps on theCoastal Plain in southeastern Virginia. Descriptions of the new species bring the total number of described species in the genus to 139, all but five of which are recorded from North America. Recognition of the four new species suggests that species diversity in Stygobromus is greater in shallow groundwater habitats east of the Appalachian cave and karst region than originally believed.